Kapasitas Daya Pembangkit Listrik Tenaga Mikrohidro di Alue Dua Aceh Utara - Asri asri (Jurnal Rekayasa Elektrika, 2014)
The utilization of micro hydropower plant is intended for providing electricity at Alue Dua village in North Aceh. A problem associated with the implementation of the micro-hydropower plant in the village is that the water flowrate of the run-of-river is varied at 117 litres per second during the wet season and at 36 litres per second during the dry season. This variation affects the speed of the water turbine and the capacity of power generated by its generator. Therefore to stabilize the output power and voltage of the generator during the course of the year, this paper aims to regulate the intake water flowing into the water turbine by controlling the opening vent valve from 0% up to 100% and controlling the electrical load connected to the generator. The speed of the water turbine was measured using the tachometer. It was found that the generator can produce electricity at its rated power 40 kVA during the wet season by opening the valve at 100% and at 12 kVA with the opening valve at 30% during the dry season. Opening the vent valve at 100% during the dry season can drain the water within 12 minutes